THE FLEXIBILIZATION OF LABOR RELATIONS: A STUDY ON THE IMPACTS AND CHALLENGES IN BRAZILIAN LABOR LAW. (REMUNOM, 2025)
In recent decades, the Brazilian labor market has undergone profound transformations, driven by economic, technological, and social factors. In this context, the flexibilization of labor relations has emerged as a response to the need to adapt to a globalized economy, reduce unemployment, and increase business competitiveness. With the enactment of Law No. 13.467/2017, known as the Labor Reform, the legal framework began to allow greater freedom in the hiring, execution, and termination of employment contracts, introducing models such as intermittent work, remote work, outsourcing, and the strengthening of collective bargaining. While supporters argue that these measures promote the modernization of labor relations and encourage formal employment, there are strong criticisms regarding job insecurity, the weakening of legal protections, and the potential erosion of consolidated social rights. In light of this scenario, this article aims to analyze the impacts and challenges posed by flexibilization in Brazilian Labor Law, with a focus on the consequences of the Labor Reform. The research is based on bibliographic review and normative analysis, seeking to understand to what extent legislative changes reconcile the need for adaptation to new labor dynamics with the preservation of workers' dignity and the fundamental principles of social justice.